Variability of Allium sativum group sativum clones in Mendoza, Argentina - Portela, Jose Antonio; Lanzavechia, Silvina Beatriz; Burba, Jose Luis; Lucero, C.; Ocañas, Ramon Orlando (International Society for Horticultural Science, 2021)
Presentado al VI International Symposium on Edible Alliaceae